Patterns for Beginning Programmers - Bernstein, David (Open textbook library., 2022)
Programming patterns are solutions to problems that require the creation of a small fragment of code that will be part of a larger program. Hence, this book is about teaching you how to write such fragments of code. However, it is not about teaching you the syntax of the statements in the fragments, it assumes that you already know the syntax. Instead, it is about finding solutions to problems that arise when first learning to program.